The armed conflict and violence in school textbooks of Social Sciences: looks from its research field (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2018)
This article brings together the most relevant national and international research on the treatment given in school textbooks of social sciences to the issues of armed conflict and violence from four groups related to: 1). School textbooks and ideology that brings together research that addresses the influence of various political regimes in the production of textbooks either in times of conflict or on issues of recent history; 2) School textbooks and curriculum that groups works on school textbooks and the knowledge circulating there about conflict and violence. 3) School textbooks and images of violence that presents works related to views or representations that disseminate school textbooks in relation to certain events or actors linked to violence or conflict. And 4). School textbooks and comparative memory that contain research that compares school texts among themselves or with other productions (written and / or artistic) to consolidate diverse ethical and political views of the facts of violence and conflict.
Keywords: school textbooks; armed conflict; violence; social science teaching